Peran Pembelajaran Aqidah Akhlak dalam Membentuk Karakter Disiplin Siswa di MTs Yapika (Yayasan Pendidikan Al-Istiqomah Karyaguna) Kabupaten Kebumen - Fahmi Zaenal Abidin; Sri Haryanto; Salis Irvan Fuadi (IHSANIKA : Jurnal Pendidikan Agama Islam, 2025)
This research aims to describe and analyze the efforts to build students' disciplined character through the study of Aqidah Akhlak at MTs YAPIKA Petanahan Kebumen. To identify the issues in this research, the author employs a descriptive qualitative research methodology with a case study method. The results of this study indicate that: 1) it shows that the teaching of Aqidah Akhlak at MTs YAPIKA Kebumen has a significant contribution to forming and strengthening students' disciplined character. 2) The strategies used by Aqidah Akhlak teachers include: integrating discipline values into the teaching material, instilling exemplary behavior through the teachers' attitudes, applying participatory learning methods, and providing reinforcement through religious advice and habits such as arriving on time and reciting Asmaul Husna.3) For the internal inhibiting factors, there are still some students who have a low level of awareness regarding the importance of discipline, both in terms of time, assignments, and adherence to school and religious rules. Furthermore, habituation activities such as reading Asmaul Husna and class duty are sometimes not maximally supervised, causing students to carry them out insincerely and merely as a formality. The supporting factors in this activity are: The Aqidah Akhlak teacher at MTs YAPIKA Petanahan not only conveys the material theoretically, but also provides real examples in disciplined attitudes and behaviors. The teacher arrives on time, is friendly yet firm, and is consistent in guiding students both in and out of the classroom.